Modulation of bradykinin-induced intracellular Ca2+ oscillations in v-Ki-ras-transformed fibroblasts - Fu Tao; Gu Zhen-lun; Xu Yong-hua (Acta Pharmacologica Sinica, 2016)
Modulation of bradykinin (BK)-induced intracellular Ca2+ oscillations was investigated with single cell Ca2+ analysis in v-Ki-ras-transformed NIH3T3 fibroblasts. The Ca2+ oscillations were inhibited by the addition of a specific antagonist for subtype 2 of BK receptors (B2 receptor), not the antagonist for B1 receptor. Decrease of the extracellular Ca2+ concentration suppressed the [Ca2+]i oscillations and application of thapsigargin dissipated the [Ca2+]i oscillations. These findings suggest that the continuous activation of B2 receptor leading to the fluctuations of both Ca2+ influx which refills the internal Ca2+ stores, and Ca2+ mobilization from the internal stores, is essential to the occurrence of the [Ca2+]i oscillations in these cells.